The emerging role of 12/15-lipoxygenase in ischemic stroke - Xuening Wang; Qiuji Shao; Yuan Gao (Brain Research Bulletin)
The arachidonic acid metabolic pathway is a classic inflammatory pathway. 12/15-lipoxygenase (LOX), a member of the lipoxygenase family that metabolizes arachidonic acid, has been implicated in the pathogenesis of numerous central nervous system (CNS) diseases. Ischemic stroke is a devastating disease in which the occlusion of cerebral arteries leads to a series of pathophysiological changes in brain tissue, triggering an inflammatory cascade within the brain that results in neuroinflammation. Prior research has shown that 12/15-LOX levels in the brain are elevated following stroke. In this review, we elaborate on the key pathological mechanisms that unfold following ischemic stroke, including neuroinflammation, oxidative stress, neuronal apoptosis, and blood-brain barrier disruption, and present evidence demonstrating that 12/15-LOX inhibition could be used to treat ischemic stroke through various avenues. Furthermore, we list currently available inhibitors of 12/15-LOX and the preclinical or clinical applications, offering novel insights for the early diagnosis, prognosis evaluation, and targeted therapy in neurological diseases.